Pendidikan Inklusif pada PAUD: AnalisisPermasalahan dan Solusi Berbasis StudiLiteratur - Khuru’Aini, Loeyyina; Setiyatna, Hery (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2025)
This study aims to analyze various problems and solutions in the implementation of inclusive education in Early Childhood Education (PAUD) institutions through a literature review method. Inclusive education in PAUD is an effort to provide fair and equal educational services for all children, including children with special needs. However, its implementation in the field still faces many obstacles, such as limited teacher competency, lack of facilities and infrastructure, low parental support, and suboptimal institutional policies. This study collected and analyzed ten national and international scientific articles related to the implementation of inclusion in PAUD. The results of the study indicate that the main problems lie in the aspects of human resources and policy, while the proposed solutions include improving teacher competency, strengthening collaboration between teachers and parents, and policy support from the government and educational institutions. Thus, inclusive education in PAUD can be implemented more effectively through synergy between the various parties involved.